Respiratory Outcomes in Patients Following COVID-19-Related Hospitalization: A Meta-Analysis - Guo, Tao; Jiang, Fangfang; Liu, Yufei; Zhao, Yunpeng; Li, Yiran; Wang, Yihua (Frontiers in Molecular Biosciences, 2021)
Background: To determine the respiratory outcomes in patients following COVID-19-related hospitalisation. Methods: Systematic review and meta-analysis of the literature. Results: Forced vital capacity (FVC, % of predicted): 0-3 months post discharge: 94.9, 95% CI [82.2-107.7]; 3-6 months post discharge: 99.9, 95% CI [84.8, 115.0]; > 6 months post discharge: 97.4, 95% CI [76.8-118.0]. Diffusing capacity of the lungs for carbon monoxide (DLCO, % of predicted): 0-3 months post discharge: 83.9, 95% CI [68.9-98.9]; 3-6 months post discharge: 91.2, 95% CI [74.8-107.7]; > 6 months post discharge: 97.3, 95% CI [76.7-117.9]. Percentage of patients with FVC less than 80% of predicted: 0-3 months post discharge: 10%, 95% CI [6-14%]; 3-6 months post discharge: 10%, 95% CI [2-18%]; > 6 months post discharge: 13%, 95% CI [8-18%]. Percentage of patients with DLCO less than 80% of predicted: 0-3 months post discharge: 48%, 95% CI [41-56%]; 3-6 months post discharge: 33%, 95% CI [23-44%]; > 6 months post discharge: 43%, 95% CI [22-65%]. Conclusion: The meta-analysis confirms a high prevalence of persistent lung diffusion impairment in patients following COVID-19-related hospitalisation. Routine respiratory follow-up is thus strongly recommended.